2005
DOI: 10.1309/yqbr9c05ru4dd3rn
|View full text |Cite
|
Sign up to set email alerts
|

BRAFGene Mutations Are Rare Events in Gastroenteropancreatic Neuroendocrine Tumors

Abstract: The BRAF gene, one of the human isoforms of RAF, is activated by ras, leading to cooperative effects in cells responsive to growth factor signals. We studied the frequency of BRAF and k-ras-2 mutations in primary neuroendocrine gastroenteropancreatic (GEP) tumors. Mutation analysis of the BRAF and k-ras-2 genes was performed in 40 primary neuroendocrine tumors of the GEP system. The expression of extracellular signaling-related kinase (ERK) 1/2, an important downstream point of convergence in the ras-RAF-mitog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…It should be noted that a decreased phosphorylation in p70S6K/p85S6K, two isoforms of the same kinase belonging to the same signalling pathway [45] and downstream of Akt [46], and considered a marker of Akt signalling was not observed. This suggests the principle effector is through ERK, well-known to be upregulated in SI-NENs [47,48]. A number of GPCRs activate NFκB via Gi-or Gq-dependent pathways and an intricate signalling network exists between GNA15-coupled receptors and the IKB kinase (IKK)/NFkB pathway [49].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that a decreased phosphorylation in p70S6K/p85S6K, two isoforms of the same kinase belonging to the same signalling pathway [45] and downstream of Akt [46], and considered a marker of Akt signalling was not observed. This suggests the principle effector is through ERK, well-known to be upregulated in SI-NENs [47,48]. A number of GPCRs activate NFκB via Gi-or Gq-dependent pathways and an intricate signalling network exists between GNA15-coupled receptors and the IKB kinase (IKK)/NFkB pathway [49].…”
Section: Discussionmentioning
confidence: 99%
“…Only six publications deal with the molecular mechanisms of oncogenesis and metastasis development in VIPoma, reporting no more than two cases in each publication [13-18]. The remaining publication reports on the clinical presentation, diagnostics, and therapeutic options.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining publication reports on the clinical presentation, diagnostics, and therapeutic options. Amongst others, mutations in the tumor suppression genes DPC4 [15], AIM1 (‘absent in melanoma1’) and PTPRK (receptor type protein-tyrosine phophastase kappa) [14] are shown in metastatic VIPomas while mutations of the proto oncogene BRAF known to play an important role in thyroid cancer and melanoma were not found [15,18]. A series of 35 neuroendocrine tumors of the pancreas showed that defects in DNA mismatch repair are rather rare with the limitation, that no VIPoma case was included [19].…”
Section: Discussionmentioning
confidence: 99%